2009
DOI: 10.1002/ange.200903886
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Carbon Nitride Structure for Visible‐Light Catalysis by Copolymerization

Abstract: Strukturell ähnlich zu Liebigs Melon (Poly(aminoimino)heptazin) sind Kohlenstoffnitrid‐Photokatalysatoren (siehe Formel), die durch direkte Copolymerisation von Dicyandiamid mit Barbitursäure erhalten werden können. Das Bild zeigt, wie sich die optische Absorption der Produkte bei steigendem Barbitursäure‐Anteil in der Copolymerisationsmischung (Pfeile) weiter in die sichtbare Region ausdehnt, was von Vorteil für Solarenergieanwendungen ist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
188
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(205 citation statements)
references
References 33 publications
9
188
0
8
Order By: Relevance
“…The application of these mono-disperse hollow conjugated semiconductor vesicles has been demonstrated using a photocatalytic hydrogen-evolution assay, and their advantages from the inner optical reflection and improved structure condensation provide a remarkably increased photochemical activity, reaching an overall AQY of approximately 7.5%. Although the blue shift of the band gap, which was associated to either a quantum size effect or enhanced H-type interlayer packing, was unwanted, further chemical control, such as extending the pi system by anchoring aromatic motifs, are already available to expand the visible absorption, for example, through copolymerisation 46,47 . Hybrid nanoarchitectures based on finely tuned polymeric carbon nitride capsules provide a valuable platform for constructing highly organized photosynthetic systems for the efficient and sustained utilization of solar radiation after the controlled deposition of a cocatalyst onto the exterior and/or interior surfaces and the construction of a dyadic layer to promote exciton dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…The application of these mono-disperse hollow conjugated semiconductor vesicles has been demonstrated using a photocatalytic hydrogen-evolution assay, and their advantages from the inner optical reflection and improved structure condensation provide a remarkably increased photochemical activity, reaching an overall AQY of approximately 7.5%. Although the blue shift of the band gap, which was associated to either a quantum size effect or enhanced H-type interlayer packing, was unwanted, further chemical control, such as extending the pi system by anchoring aromatic motifs, are already available to expand the visible absorption, for example, through copolymerisation 46,47 . Hybrid nanoarchitectures based on finely tuned polymeric carbon nitride capsules provide a valuable platform for constructing highly organized photosynthetic systems for the efficient and sustained utilization of solar radiation after the controlled deposition of a cocatalyst onto the exterior and/or interior surfaces and the construction of a dyadic layer to promote exciton dissociation.…”
Section: Discussionmentioning
confidence: 99%
“…The most efficient metal-free photocatalyst is the graphitic carbon nitride (g-C 3 N 4 ). [74][75][76][77][78] For instance, Wang et al [79] reported that the carbon nitride (C 3 N 4 ) polymer can be easily modified by standard organic protocols. The copolymerization with barbituric acid was studied and realized the continuous band structure modification.…”
Section: Band Structure Engineering Through Crystal Structure Modificmentioning
confidence: 99%
“…Due to the strong C-N good chemical stability and thermal stability (up to 600 o C). All these merits make it to be an idea material for the application in hydrogen evolution 19,[21][22][23][24][25][26][27][28][29][30] as well as environmental pollutant degradation. [31][32][33][34][35][36][37][38][39][40] g-C 3 N 4 is a semiconductor with a band gap of 2.7 eV, with a VB level suitable for hydrogen and oxygen evolution both.…”
Section: Introductionmentioning
confidence: 99%